2015
DOI: 10.3390/ijns1020057
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Glutaric Aciduria Type I: Benefits and limitations

Abstract: More than 15 years ago glutaric aciduria type I has been included in newborn screening programmes and pilot studies evaluating the potential benefit of early diagnosis and start of metabolic treatment for patients with this disease have been initiated. At that time many important questions on epidemiology, diagnostic quality, natural history, treatment, and cost effectiveness were not sufficiently answered. In particular, it was rather unknown whether early treatment improves the outcome. After implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Since neurological symptoms such as developmental delay and movement disorders are most commonly found in OAD patients and often manifest early in the disease course (Kölker et al 2015b), we mostly focused on the neurological outcome. In line with previous studies (Bijarnia et al 2008;Boneh et al 2008;Heringer et al 2010Heringer et al , 2015Kölker et al 2007;S t r a u s s et al 2007;V i a ue ta l2012), we showed that NBS improves the neurological outcome in GA1 patients. Similarly, NBS reduces the occurrence of movement disorders, and increases normal motor development in MMA-Cbl − patients (n = 31).…”
Section: Discussionsupporting
confidence: 93%
“…Since neurological symptoms such as developmental delay and movement disorders are most commonly found in OAD patients and often manifest early in the disease course (Kölker et al 2015b), we mostly focused on the neurological outcome. In line with previous studies (Bijarnia et al 2008;Boneh et al 2008;Heringer et al 2010Heringer et al , 2015Kölker et al 2007;S t r a u s s et al 2007;V i a ue ta l2012), we showed that NBS improves the neurological outcome in GA1 patients. Similarly, NBS reduces the occurrence of movement disorders, and increases normal motor development in MMA-Cbl − patients (n = 31).…”
Section: Discussionsupporting
confidence: 93%
“…11 The mutant "T" allele frequency for R402W mutation in this study was found to be 17% (16/96), which is similar to the frequency range reported among Europeans (10-20%). 21 A recent study by Gupta et al, 16 with 17 GA-I patients from India, showed mutant allelic frequency of 23.5% (8/34) for R402W mutation and concluded that this is the most commonly occurring mutation in their cohort. Our previous study with 30 GA-I patients screened for R402W mutation showed allelic frequency of 15% (9/60).…”
Section: Discussionmentioning
confidence: 96%
“…The experience with NBS in other countries showed that the majority of newborns are asymptomatic though a macrocephaly and neurological symptoms such as hypotonia and asymmetric posturing are often present (23). Therefore, the NBS is even more important in a high-risk population such as: the Amish Community in Pennsylvania (USA), the original inhabitants of the Canadian province of Ontario and Manitoba called Oji-Cree (Canada), the Irish travellers (U.K.), the Lumbee tribe in North Carolina (USA) and the indigenous inhabitants of South Africa (17), where the prevalence of GAI should be up to 1: 300. The occurrence of GAI in state of Andhra Pradesh in India appears to be relatively more frequent caused by a higher rate of consanguinity and endogamous marriages (18).…”
Section: Discussionmentioning
confidence: 99%
“…At present, for this purpose (1)H magnetic resonance spectroscopy with the metabolite fi ndings correlating with biochemical phenotype and duration of the disease can be applied (34). Also, it is necessary to consider the possibility of incorrect diagnosis that could be caused by glutaric aciduria type II (multiple acyl-CoA dehydrogenase defi ciency), pseudoglutarylcarnitinaemia (caused by interfering acylcarnitines identifi ed as hydroxyoctanoylcarnitine and hydroxydecanoylcarnitine) in patients with medium-chain acyl-CoA dehydrogenase (MCAD) defi ciency as well as in newborns with renal failure, and maternal aciduria glutaric type I (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation